Imperatorin ameliorates pulmonary fibrosis via GDF15 expression - Tsai, Cheng-Fang; Chen, Yen-Chang; Li, Ya-Zhen; Wu, Chen-Teng; Chang, Pei-Chun; Yeh, Wei-Lan (Frontiers in Pharmacology, 2023)
Background: Pulmonary fibrosis features in damaged pulmonary structure or over-produced extracellular matrix and impaired lung function that lead to respiratory failure and death. Pro-fibrotic factors secretion, fibroblasts transformation into myofibroblasts, and accumulation of matrix protein characterize fibrotic lungs. Hypothesis/Purpose: Imperatorin has anti-inflammatory effects in alveolar macrophages against acute lung injury. We attempt to evaluate the properties of imperatorin on the basis of fibroblasts. Methods: In vitro, zymosan was introduced to provoke pro-fibrotic responses in NIH/3T3 or MRC-5 pulmonary fibroblasts. The treatment of imperatorin was given for examining its effects against fibrosis. Mice was stimulated by bleomycin, and imperatorin was administer to evaluate the prophylactic potential in vivo. Results: Zymosan-increased connective tissue growth factor (CTGF), α-smooth muscle actin (α-SMA), and collagen protein expressions were decreased by imperatorin in fibroblasts. Zymosan induced the activity of transglutaminase 2 (TGase 2) and lysyl oxidase (LOX), which are also inhibited by the treatment of imperatorin. Imperatorin alone enhanced sirtuins 1 (SIRT1) activity and growth differentiation factor 15 (GDF15) secretion in fibroblasts through LKB1/AMPK/CREB pathways. In addition, GDF15 exerted a beneficial effect by reducing protein expressions of CTGF, α-SMA, collagen, and the activities of TGase and LOX. Moreover, orally administered imperatorin showed prophylactic effects in bleomycin-induced pulmonary fibrosis in mice. Conclusion: Imperatorin reduces fibrotic markers expression in fibroblasts, and also increases GDF15 secretion via LKB1/AMPK/CREB pathway that attenuating pro-fibrotic responses in vitro. Imperatorin also alleviate pulmonary fibrosis induced by bleomycin in vivo.